2023
DOI: 10.1002/jmv.28687
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant measles virus expressing prefusion spike protein stabilized by six rather than two prolines is more efficacious against SARS‐CoV‐2 infection

Abstract: Measles virus (MeV) has been an excellent vector platform for delivering vaccines against many pathogens because of its high safety and efficacy, and induction of long-lived immunity. Early in the COVID-19 pandemic, a recombinant MeV (rMeV) expressing the prefusion full-length spike protein stabilized by two prolines (TMV-083) was developed and tested in phase 1 and 1/2 clinical trials but was discontinued because of insufficient immunogenicity and a low seroconversion rate in adults. Here, we compared the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We recently showed that preS stabilized by 6 prolines (preS-6P) ( 20 ) induced six to eight times higher NAbs than preS-2P ( 21 ) in MuV-JL2 ( 18 ) and MeV ( 22 ) vectors. Therefore, we inserted a codon-optimized preS-6P gene of the Delta variant into the P–M gene junction of the MuV-JL1 genome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that preS stabilized by 6 prolines (preS-6P) ( 20 ) induced six to eight times higher NAbs than preS-2P ( 21 ) in MuV-JL2 ( 18 ) and MeV ( 22 ) vectors. Therefore, we inserted a codon-optimized preS-6P gene of the Delta variant into the P–M gene junction of the MuV-JL1 genome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, all current COVID-19 vaccines utilize the native full-length S or preS-2P as the vaccine antigen (3) . Because preS-6P has much higher protein expression and is more stable compared to preS-2P, the use of preS-6P in vaccine design will significantly enhance the efficacy and longevity of immune responses ( 18 , 20 , 22 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rMeV-based SARS-CoV-2 vaccine platform (V591) developed by Merck was announced to be discontinued in phase I and I/II clinical trials because of the insufficient immune responses and seroconversion rate [ 40 ]. Thus, they concluded that V591 was generally well tolerated but the immunogenicity was not sufficient for further development [ 41 ]. In addition, rMeV-preFS induced high levels of immune response compared with rMeV-S+SPD in hamsters.…”
Section: Discussionmentioning
confidence: 99%